ANALISIS TATA KELOLA (MANAJEMEN) PEMERINTAHAN DARI PERSPEKTIF GOOD GOVERNANCE - Ahmad Dirwan (JURNAL ILMIAH HUKUM DIRGANTARA, 2013)
As stated in the preamble of the 1945 Constitution, the goal of our states is to form a government of the state of Indonesia which shall protect all the Indonesian people and the entire country, promote the general welfare, the intellectual life of the nation and participate in the establishment of world peace. This understanding is based on the need of clean government and to accommodate the principles of good governance. Currently, our government has not been fully able to protect and carry out its functions as mandated by the 1945 opening which is stated above . This is consistent with the results of research on Indonesia which governance has not improved significantly and has not been consistent after 15 years of reform. The data is processed by comparing the implementation of data governance at the beginning of the reforming process (1996/1998) and the 2009-2014 strategic plan (drawn from the data transparency of Worldwide Governance Indicators Projects 2010 and Kompas May 20, 2013).